The Intellectual Network of Shaykh Abdusshamad Al-Falimbani and His Contribution in Grounding Islam in Indonesian Archipelago at 18th Century AD - Dzulkifli Hadi Imawan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2018)
This paper aimed to discuss about the intellectual network of Shaykh Abdusshamad al-Falimbani and his contribution to the grounding of Islam in Indonesia during the 18th century. He was one of the great scholars who had an intellectual network in Indonesian archipelago and Arabian Peninsula. He played a big role in the dissemination of Islamic lecture in both countries. His impact was widely documented in the biographies of the Arabic figure (tarajim) and isnad. Therefore, this study attempted to trace his intellectual network and his contributions to the Islamic world, especially in Indonesia at 18th century. This study used a literature study on the biography of Shaykh Abdusshamad al-Falimbani, information was obtained from literature sources related to him and his work. The results of this study revealed that Shaykh Abdusshamad al-Falimbani had a lot of intellectual networks that connected the Indonesian and Arabian Peninsula’s scholars and played a major role in grounding Islam in Indonesia. This was carried out through the caderization of his students and the publication of his writings, which brought by his students to Indonesia. His works encouraged Indonesian Muslims to adhere to the teachings of Ahlu al-Sunnah wa al-Jama'ah, hold on to syafi’i madzhab, and accept the sunni tasawwuf as the teachings of the Prophet.